2007
DOI: 10.1159/000104177
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of Luteinizing Hormone Pulse Frequency in Adolescent Girls with a History of Central Precocious Puberty with versus without Hyperandrogenism

Abstract: Some adolescents with a history of idiopathic central precocious puberty (ICPP) develop hyperandrogenism. Hypothesis: Luteinizing hormone (LH) hypersecretion could be a common mechanism underlying ICPP and polycystic ovary syndrome. Aim: To explore the GnRH-LH axis in those patients. Design: To compare overnight LH secretion in 7 healthy adolescents (CG) with that in patients with prior ICPP [5 with (CPPA) and 7 without (CPPB) hyperandrogenism]. To analyze daytime LH secretion in those patients. Methods: LH se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
12
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 50 publications
3
12
0
Order By: Relevance
“…Regarding clinical hyperandrogenism, the prevalence of hirsutism (23%) was similar to that reported by other authors in patients who had ICPP (14) and higher than the 12% reported for normal women (32).…”
Section: Hyperandrogenismsupporting
confidence: 88%
See 1 more Smart Citation
“…Regarding clinical hyperandrogenism, the prevalence of hirsutism (23%) was similar to that reported by other authors in patients who had ICPP (14) and higher than the 12% reported for normal women (32).…”
Section: Hyperandrogenismsupporting
confidence: 88%
“…Idiopathic central precocious puberty (ICPP) resembles PCOS in that it is characterized by increased LH levels and pulse frequency (12)(13)(14). Case observations have prompted speculation that an underlying neuroendocrine dysfunction manifests first as ICPP and later as PCOS (15).…”
mentioning
confidence: 99%
“…In contrast, a large body of evidence has shown that GNRHa therapy does not provide similar beneficial effects in girls with early puberty (1,4). Furthermore, a high risk of developing polycystic ovary syndrome (PCOS) has been postulated in girls with CPP (5)(6)(7)(8)(9). PCOS is a heterogeneous endocrinopathy characterized by abnormal gonadotropin release and dysregulation of steroidogenesis (10), and based on the presence or absence of four key features: menstrual dysfunction, clinical and/or biochemical signs of androgen excess, and polycystic ovaries (11).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, circulating FSH levels have been reported to be low to normal in both PA female monkeys [12,20] and in women with PCOS [14,21], thereby elevating the serum LH:FSH ratio. It has been proposed that LH hypersecretion in PCOS may originate during adolescence, initially caused by hyperandrogenism and then, potentially, contributing to peripubertal hyperandrogenism (as in some adolescents with PCOS [22,23]). Such neuroendocrine dysfunction, however, may originate in utero from androgen/estrogen-induced changes in the fetal hypothalamo-pituitary axis [4,[24][25][26][27] before any subsequent peripubertal dysfunction.…”
Section: Introductionmentioning
confidence: 99%